Penerapan Pembagian Bagian Anak Perempuan Pasal 176 Kompilasi Hukum Islam (KHI) - Syuhada' Syuhada' (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2019)
Abstract: The Science of Far'idh is discussing or regulating various matters in the distribution of inheritance to those entitled to receive it from the basic provisions stipulated in the Koran, the sunnah of the Holy Prophet. and ulam agreement '. The object is the distribution of inheritance for heirs who are entitled to receive. The benefit of this knowledge is that it can provide heir rights to inheritance (HP) in accordance with Islamic Sharia guidance based on the Qur'an, Al-Hadit, Al-'Ijmâ ‘and Al-Qiyâs. KHI article 176